High Performance Liquid Chromatographic Analysis of Emblica Officinalis for Its Gallic Acid Content Obtained from Various Geographical Sources - S.Manimaran; S.Kokila Vani; P.Jeevan Prasath; C.Manojkumar; C.Singaravelan; L.Monisha; G.Arunachalam; R. Joseph Sahaya Raja2; R.Prasath (International Journal of Allied Medical Sciences and Clinical Research, 2021)
Standardization of herbal medicine is the process of prescribing a set of standards or inherent characteristics, constant parameters, definitive quantitative and qualitative values that carry on assurance of quality, safety, efficacy and reproducibility. The objective of present study is to carry out the standardization of herbal raw material Emblica officinalis locally called as Amla for its gallic acid content to check the content uniformity obtained from various soils by High Performance Liquid Chromatographic Technique (HPLC). The collected fresh fruits were cut in to small pieces, dried under shade and made to fine powder. The powdered raw materials were subjected to HPLC analysis to estimate the gallic acid content. The percentage of gallic acid was estimated by comparing the peak area of standard and the same present in the samples. The results reveal that there are lots of variations between the samples and the percentage of gallic acid is not uniform in all the collected samples. Based on the current research we strongly recommend to implement the Good Agricultural and Collection Practices (GACP) during medicinal plants cultivation to ensure the quality of herbal raw materials and also increasing the yield of the crop. The quality of raw materials will increase the trade of medicinal plants due to uniform content of phytoconstituents which is responsible for the therapeutic activity.